Pour ne pas chanter idiote. Quand les Cultural Studies et la perspective féministe se marient - Boisclair, Isabelle (Françoise Stéréo, 2014)
Keywords: Pas de lien web

Women in Leonard Cohen's Work - Álvarez Pérez, Maria Icíar (Multidisciplinary Views on Popular Culture: Proceedings of the 5th International Selicup Conference, 2014)

Pétassetissité : Contenu explicite et lyrisme sexuel dans le hip-hop au Québec - Lamort, Kapois (Les boss du Québec. R.A.P. du fleur de lysée. Analyse socio-historique et sociologique du hip-hop dans la société québécoise, 2014)
Keywords: Italique avant les deux-points

Interpreting Brazilianness: Reception and Representation in the Brazilian Music Scenes of Toronto and Montreal - Mercier, Catherine G. (Université de Toronto, 2014)
In Toronto and Montreal, Brazilian popular music performances constitute a context for intercultural encounter. Performances offer Brazilians the opportunity to present their culture of origin while emphasising their identification with it. The issue of representation is quite complex, however, due to the involvement of a majority of non-Brazilian musicians, audience members, artistic directors, producers, promoters, and journalists. This dissertation focuses on music reception and cultural representation and how these may influence each other after music has been decontextualised and recontextualised. I look closely at local non-Brazilian audiences possessing different degrees of familiarity with Brazilian music, and I demonstrate how cultural stereotypes influence their conceptions and expectations of Brazilian music, culture, and people. I argue that a desire for cultural difference and the exotic, encouraged by discourses of cultural diversity, influences the reception of performances. I suggest that, through the privileged gaze of non-Brazilian attendees, performances may be adjusted to correspond to audience fantasies of Brazil. Some non-Brazilians would like to become knowledgeable of, and even intimate with Brazilian culture, which would satisfy their desire to be cosmopolitan. However, pleasure frequently matters more to them than a nuanced understanding of Brazilian culture; this explains, I contend, why some Torontonians and Montrealers have become comfortable with essentialist and stereotypical representations. I examine how some non-Brazilian musicians, promoters, and band agents reinforce mythologies of Brazil to meet audience demands and sometimes to satisfy their own fantasies. I analyse the reproduction of similarly problematic discourses on Brazil in the presentations of Brazilian artists as both a form of autoexoticism and a particular type of tactical or strategic essentialism. Rather than to represent and understand Brazilian culture, I argue that, through local music performances, Brazilians and non-Brazilians in Toronto and Montreal interpret Brazilianness.

Le voyage, la danse et la représentation des femmes dans la culture de grande consommation (1936-1947) - Savoie, Chantal (Les Cahiers de l'IREF, 2014)